Metal-oxide interfaces and additive engineering for high performance perovskite solar cells - Ioakeimidis, Apostolos (My University, 2021)
The need for renewable energy sources has become a necessity for a prosperous future of human society. Moreover, for the establishment of renewable technologies it is demanded to lower even more the cost. Thus, perovskite solar cells, as a promising candidate for the next generation PVs, require new materials and processes in order to increase the reliability and power conversion efficiency while also lower the cost enabling perovskite PVs to become a competitive, mainstream PV technology. In this Thesis, it is first shown the fabrication of metal-oxide NiCo2O4 thin film using doctor blade coating, which is synthesized by the low-energy demanding synthesis of solution combustion. The film is introduced as an efficient hole transporting layer (HTL) layer in a 230 nm thick MAPbI3 perovskite active layer for the fabrication of solar cells. The devices deliver a PCE in the range of 15.5 %, with negligible hysteresis for a 15 nm optimum thickness NiCo2O4 layer. A thicker MAPbI3 perovskite layer (~350 nm) was applied to enhance the PCE of the devices, following the literature reported optimum thickness for the particular perovskite formulation. The resulted perovskite solar cells exhibited a lower PCE mainly due to a reduction of the fill factor and Voc, ascribed to higher recombination at the NiCo2O4/perovskite interface given that a higher number of hole charge carriers reach the interface before they are collected. To overcome this limitation NiCo2O4 is further modified by co-doping with Li and Cu improving the selectivity and transport properties of the contacts by proper modifications of the energetic levels and by increasing the electrical conductivity of the charge carriers, respectively. The engineered Cu, Li doped NiCo2O4 resulted in higher PCE perovskite solar cells (16.5%) due to improved interface properties. Then, by deeper investigation of the solution combustion synthesis method, we study a range of applied temperatures (150, 200 and 300 oC) and fuel concentration (acetylacetonate) (without, 0.1 and 1.5 ratio to oxidizer) for the fabrication of metal-oxide Cu:NiOx. The objective was to identify the lowest required temperature for the synthesis of functional and high performing Cu:NiOx HTL for use as HTL in perovskite solar cells. It is revealed that solution combustion synthesis behavior of Cu:NiOx films is different compared to bulk analogues, supporting reports which concluded that the low temperature solution combustion synthesis of crystalline materials is unlikely to occur in thin films. Specifically, we show that the required temperature for the synthesis of crystalline Cu:NiOx films in around 300 oC which is higher compared to bulk analogue where a complete combustion process occurs at ~150 oC resulting in crystalline bulk forms. The various temperature and fuel concentration processed Cu:NiOx films were introduces in Cs0.04(MA0.17FA0.83)0.96 Pb(I0.83Br0.17)3 based perovskite solar cells showing that the devices annealed at temperatures 150 and 200 oC delivered limited PCE solar cells, while on the other hand the 300 oC annealed Cu:NiOx resulted in high performing perovskite solar cells. The highest performing devices obtained for Cu:NiOx precursor ink annealed at 300oC containing 0.1 ration of acetyl acetonate delivering a PCE of 16.58 %. Finally, by applying the optimized conditions for the combustion synthesis (300 oC and 0.1 ratio acetylacetonate) undoped NiOx films are used as HTL in perovskite solar cells based on the methylammonium free perovskite formulation CsFAPBI3 where the hybrid perovskite active layer was engineered by molecular additive to improve the reliability and the humidity degradation resistance. Nitrobenzene was selected as additive (1% v/v) considering the nitro group which can interact with PbI6 cage of the perovskite leading to a passivation effect and the benzene group is a hydrophobic group that can protect from moisture ingress. The engineered devices delivered a higher Voc compared to unmodified reference with the best devices PCE in the range of 18 %, ascribed to structural defect passivation. Also, the additive based devices delivered a higher mean PCE with much narrower distribution due to reduced roughness/thickness inhomogeneity of the perovskite layer. The additive usage improved the air stability with the most stable device retaining over 85% of its initial PCE after 1500 h in air, whereas the additive-free devices decline by more than 65%. Improved humidity degradation resistance was further demonstrated by accelerated humidity study (75% relative humidity (RH)) confirming the enhancement of devices stability owing to the defect passivation and inhibition of moisture permeation effects induced by the use of Nitrobenzene.
Keywords: Perovksite solar cells; Interface engineering; Metal oxide interfaces; Solution combustion synthesis; perovskite doping